Bubble Behaviors in a Dense Gas‐Solids Fluidized Bed: Analysis of Pressure Fluctuation. Issue 9 (9th August 2022) - Ma, Zhunzhun; Ma, Hongfang; Qian, Weixin; Zhang, Haitao; Sun, Qiwen; Ying, Weiyong
Abstract: The pressure signals were analyzed by time‐domain and frequency‐domain methods, including standard deviation, autocorrelation function, and power spectral density function, to investigate the bubble behavior and determine the regime transition. Results indicated that the autocorrelation function of pressure signals derived from bubbles was periodic fluctuation. The periodic nature of the autocorrelation function disappeared and the dominant frequency increased when the transition from bubbling to the turbulent regime occurred. The decrease of static bed height facilitated the explosion of bubbles, which accelerated the transition from the bubbling to the turbulent regime. The fluidization index was used as an indicator for the bubble state in the dense fluidized bed. Abstract : The fluidization index is defined as the ratio of standard deviation to the dominant frequency, which could be used to determine the fluidization regime and identify the bubble state in a dense gas‐fluidized bed. The differential pressure was measured at different superficial gas velocities and static bed heights. The pressure signals were analyzed by time‐domain and frequency‐domain methods.